The Sisters Club - McDonald, Megan; Consolazio, Pamela A. (Cambridge : Candlewick Press, 2008)
Stevie Reel feels like she's the glue holding her family together, expecially since Boss Queen Alex has gotten so wrapped up in her school play - and her leading man - that she doesn't have time for the Sisters Club. Is it up to the middle-sister Stevie to save the day? Dive into the real-life ups and downs of sisterhood with the author of the best-selling Judy Moody series.
Accelerated Reader AR
Keywords: Clubs -- Fiction; Sisters -- Fiction; Acting -- Fiction; Family life -- Fiction; Humorous stories; Oregon -- Fiction